2019
DOI: 10.1177/1071100719856888
|View full text |Cite
|
Sign up to set email alerts
|

Health and Quality of Life Outcomes Among Patients Undergoing Surgery for End-Stage Ankle Arthritis

Abstract: Background:There is little research investigating which aspects of health-related quality of life change following ankle arthrodesis and total ankle replacement surgery. The objective of this study was to report on statistically and clinically relevant changes in multiple dimensions of health-related quality of life among patients undergoing ankle replacement or fusion surgery.Methods:This study was based on a prospective sample of ankle arthrodesis and total ankle replacement patients. Participants complete t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 57 publications
1
18
0
3
Order By: Relevance
“…In contrast, prior investigations have reported that referral to nursing or rehabilitation facilities following TAA approached 20%, and that PT use following TAA approached 10%. 3,30 However, Rajapakshe et al 30 acknowledged that PT use following TAA in their study was likely underestimated. To this point, nearly 90% of our sample received several PT visits (Table 2).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In contrast, prior investigations have reported that referral to nursing or rehabilitation facilities following TAA approached 20%, and that PT use following TAA approached 10%. 3,30 However, Rajapakshe et al 30 acknowledged that PT use following TAA in their study was likely underestimated. To this point, nearly 90% of our sample received several PT visits (Table 2).…”
Section: Discussionmentioning
confidence: 95%
“…11,18,28 Relatively few studies have considered overall health or multiple domains of health. 23,24,30,34,35 One option to efficiently characterize patient health status is the Patient-Reported Measurement Information System (PROMIS). In reflection of the biopsychosocial model of care, PROMIS outcome measures include multiple domains of health to provide person-centered assessments of function (physical), symptoms (psychological), and social impact, which can be compared to population mean values.…”
Section: Introductionmentioning
confidence: 99%
“…É possível indicar o procedimento para pacientes com OA grave sem o perfil descrito previamente, mas nesse cenário as taxas de complicações como infecção, deiscência, dor residual, amplitude de movimento reduzida e taxas de reoperação são elevadas. [59][60][61] São contraindicações absolutas à artroplastia total do tornozelo (ATT):…”
Section: Realizar Os Procedimentos Adicionais Quando Necessáriosunclassified
“…As vias de acesso possíveis são via anterior ou lateral transfibular. [59][60][61] Os estudos com ATT revelam melhora clínica e dos escores de dor em até 64% dos casos. A ATT com o uso dos implantes mais modernos mostra taxas de sucesso de 70 a 90% em 10 anos.…”
Section: Realizar Os Procedimentos Adicionais Quando Necessáriosunclassified
See 1 more Smart Citation